Nitric Oxide Mediates Bleomycin‐induced Angiogenesis and Pulmonary Fibrosis via Regulation of VEGF. Issue 11 (9th September 2015) - Iyer, Anand Krishnan V.; Ramesh, Vani; Castro, Carlos A.; Kaushik, Vivek; Kulkarni, Yogesh M.; Wright, Clayton A.; Venkatadri, Rajkumar; Rojanasakul, Yon; Azad, Neelam
ABSTRACT: Pulmonary fibrosis is a progressive lung disease hallmarked by increased fibroblast proliferation, amplified levels of extracellular matrix deposition and increased angiogenesis. Although dysregulation of angiogenic mediators has been implicated in pulmonary fibrosis, the specific rate‐limiting angiogenic markers involved and their role in the progression of pulmonary fibrosis remains unclear. We demonstrate that bleomycin treatment induces angiogenesis, and inhibition of the central angiogenic mediator VEGF using anti‐VEGF antibody CBO‐P11 significantly attenuates bleomycin‐induced pulmonary fibrosis in vivo. Bleomycin‐induced nitric oxide (NO) was observed to be the key upstream regulator of VEGF via the PI3k/Akt pathway. VEGF regulated other important angiogenic proteins including PAI‐1 and IL‐8 in response to bleomycin exposure. Inhibition of NO and VEGF activity significantly mitigated bleomycin‐induced angiogenic and fibrogenic responses. NO and VEGF are key mediators of bleomycin‐induced pulmonary fibrosis, and could serve as important targets against this debilitating disease. Overall, our data suggests an important role for angiogenic mediators in the pathogenesis of bleomycin‐induced pulmonary fibrosis. J. Cell. Biochem. 116: 2484–2493, 2015. © 2015 Wiley Periodicals, Inc.